Impact of heavy metals on hormonal and immunological factors in women with repeated miscarriages - Gerhard, Ingrid; Waibel, Sylke; Daniel, Volker; Runnebaum, Benno (Human reproduction update, 1998)
In 111 women with repeated miscarriages, the urinary excretion of heavy metals was determined in a challenge test with the chelating agent 2,3-dimercaptopropane-l-sulphonic acid in addition to hormonal, chromosomal, immunological and uterine investigations. The heavy metal excretion was correlated to different immunological (natural killer cells, T cell subpopulations) and hormonal (progesterone, oestradiol, prolactin, thyroid stimulating hormone) parameters. We conclude that heavy metals seem to have a negative impact on ovarian as well as on pituitary function. The heavy metal-induced immunological changes may interfere with the physiological adaptation of the immune system to the state of pregnancy with the result of a miscarriage. The observed heavy metal-induced hormonal and immunological changes may be important factors in the pathogenesis of repeated miscarriages.Key words:DMPS testing/heavy metals/immunology/ infertility/repeated miscarriages
Gesehen am 09.04.2025